2016
DOI: 10.1136/bmjopen-2015-010904
|View full text |Cite
|
Sign up to set email alerts
|

Are schools and alcohol a good mix? A qualitative study of school principals' experiences of adults' alcohol use in Australian secondary schools

Abstract: Objective Parents, schools and the broader community influence children's socialisation to alcohol. In Australia, the UK and the USA, there have been media reports of adults consuming alcohol at family-focused school events such as fairs and graduations. The aim of this qualitative study was to describe school principals' experiences of adults' use of alcohol at school events, when children are present. Design/setting/participants A qualitative study was undertaken. Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…This is especially critical in contexts where there are large numbers of young people who are being acculturated into adult society and learning about the role of alcohol via observation. Important starting points include policies that prevent adults from consuming alcohol at school events where children are present ( 49 ) and university policies that reduce students' exposure to alcohol on campus ( 50 , 51 ). Other potential opportunities include policies relating to the service of alcohol at conferences and other work-related events ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially critical in contexts where there are large numbers of young people who are being acculturated into adult society and learning about the role of alcohol via observation. Important starting points include policies that prevent adults from consuming alcohol at school events where children are present ( 49 ) and university policies that reduce students' exposure to alcohol on campus ( 50 , 51 ). Other potential opportunities include policies relating to the service of alcohol at conferences and other work-related events ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a discrepancy between the permissive nature of adult drinking at school events and attitudes towards 'serving alcohol to adults that might include students who are over 18 years at school celebrations', with the latter being far less supported by the parents in this study. Given the frequency at which such alcohol consumption occurs however (Ward et al, 2016a, Ward et al, 2016b, it could be that this response is particularly negative due to the stipulation in the question, that over 18-year-old students might also be included. Again, parents appear to be less supportive when faced with the reality of their own child drinking.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…In most Australian jurisdictions, decision-making about alcohol consumption at school events and the promotion of alcohol in fundraising efforts are largely the responsibility of school principals and school councils (Ward et al , 2014). Several Australian studies have reported on the attitudes and experiences of school principals regarding the promotion and adults' use of alcohol on school premises and demonstrate that adults' alcohol use at school events is common (Ward et al , 2016a, 2016b). In a survey of 241 secondary school principals in New South Wales and Victoria, 36% reported at least one event where alcohol was consumed in the presence of students in the previous year, and 17% reported offering alcohol as a prize for a school fundraiser (Ward et al , 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Výzkumy realizované mezi řediteli doporučují, aby učitelé a dospělí byli vždy dobrým příkladem a sami se konzumaci alkoholu před studenty zřekli (např. na studentských akcích) (Ward, Buykx, Munro, & Wiggers, 2016). Drogová prevence musí být podpořena dalšími institucemi a aktéry.…”
Section: Výsledky Rešeršeunclassified